Analisis Kepercayaan Pengguna Paylater pada Shopee dan Tokopedia - Surya Rodoli Pasaribu; Agung Kresnamurti Rivai P; Rahmi (Univiversitas Dr. Djar Wattiheluw, 2025)
This research aims to find out how customer trust in using paylaters is described and what factors customers consider when using Shopee and Tokopedia paylaters, where a survey was conducted among students at the Faculty of Economics, Jakarta State University. The resource persons for this research were 10 students from the Faculty of Economics, Jakarta State University using the direct interview method. This research uses data collection techniques in the form of observation, interviews and documentation. This research uses data analysis techniques with data reduction, data presentation, and drawing conclusions. The results of the research found that there were four descriptions of user confidence in using paylater among students at Jakarta State University. These four images are company credibility, company integrity, company good intentions, and how the company can solve problems. Factors considered by paylater users are security, reputation, compliance with laws and regulations, and competence. It is hoped that this study can be used by companies as a basis for developing marketing and sales strategies through user trust.